The effect of early measles vaccination at 4.5 months of age on growth at 9 and 24 months of age in a randomized trial in Guinea-Bissau. Issue 1 (December 2016) - Rasmussen, S.; Biering-Sørensen, S.; Byberg, S.; Andersen, A.; Bjerregaard-Andersen, M.; Rodrigues, A.; Benn, C.; Martins, C.; Aaby, P.
Abstract Background Providing an early, additional measles vaccine (MV) at 4.5 months of age has been shown to reduce child mortality in low-income countries. We studied the effects on growth at 9 and 24 months of age. Methods A randomized controlled trial was conducted in Guinea-Bissau from 2003–2007 including 6, 648 children. Children were randomized 1:1:1 to receive Edmonston-Zagreb measles vaccine at 4.5 and 9 months of age (group A), no vaccine at 4.5 months and Edmonston-Zagreb measles vaccine at 9 months (group B), or no vaccine at 4.5 months and Schwarz measles vaccine at 9 months (group C) Data on anthropometrics were obtained at enrolment at 4.5 months of age and again at 9 and 24 months of age. Analyses were stratified by sex, season of enrolment, and neonatal vitamin A supplementation (NVAS) status, as all these factors have been shown to modify the effect of early MV on mortality. Results Overall there was no effect of early MV on anthropometry at 9 months. At 24 months children who had received early MV had a significantly larger mid-upper-arm-circumference (MUAC/in cm) (Difference = 0.08; 95% CI (0.02;0.14)) compared with children in the control group; this effect was most pronounced among girls (0.12 (0.03;0.20)). The effect of early MV on MUAC remained significant in the dry season and in girls who received placebo rather than NVAS. Conclusion Early MV was associated with a larger MUAC particularly in girls. These results indicate that a two-dose measles vaccination schedule might not only reduce child mortality but also improve growth. Trial registration ClinicalTrials.govNCT00168558 . Registered September 9, 2005, retrospectively registered